2023
DOI: 10.1002/mds.29410
|View full text |Cite
|
Sign up to set email alerts
|

Levodopa Dose Equivalency in Parkinson's Disease: Updated Systematic Review and Proposals

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 101 publications
(32 citation statements)
references
References 74 publications
0
21
0
Order By: Relevance
“…On the basis of previously published conversion methods, we report motor examination as UPDRS III scores to help interpret the data. The levodopa equivalent daily dose (LEDD) was calculated according to the method by Jost et al The total electrical energy delivered (TEED) was calculated using an established method by Koss et al, assuming a standard impedance of 1000Ω …”
Section: Methodsmentioning
confidence: 99%
“…On the basis of previously published conversion methods, we report motor examination as UPDRS III scores to help interpret the data. The levodopa equivalent daily dose (LEDD) was calculated according to the method by Jost et al The total electrical energy delivered (TEED) was calculated using an established method by Koss et al, assuming a standard impedance of 1000Ω …”
Section: Methodsmentioning
confidence: 99%
“…PD was diagnosed according to the clinical diagnostic criteria, 22 and HCs were age‐, gender‐ and education matched to patients. The Movement Disorder Society Unified Parkinson's Disease Rating Scale (MDS‐UPDRS‐III) and Hoehn and Yahr (HY) scale were adopted to assess disease severity, and the levodopa ( l ‐dopa) and the dopamine agonist equivalent daily dosages were calculated for each patient 23 …”
Section: Methodsmentioning
confidence: 99%
“…The Movement Disorder Society Unified Parkinson's Disease Rating Scale (MDS-UPDRS-III) and Hoehn and Yahr (HY) scale were adopted to assess disease severity, and the levodopa (L-dopa) and the dopamine agonist equivalent daily dosages were calculated for each patient. 23 All subjects underwent a comprehensive neuropsychological battery (level II criteria of the MDS guidelines) as previously described, 24 specifically designed to target PD-cognitive deficits, which allow us to classify patients as PD-NC, PD-MCI, or PD with dementia (PDD) (for further details refer to the Supporting Information). The present study was approved by the Venice Research Ethics Committee, Venice, Italy.…”
Section: Participants and Clinical Assessmentmentioning
confidence: 99%
“…Parkinsonian medications include levodopa, dopamine agonists, monoamine oxidase B (MAOB) inhibitors, catechol‐O‐methyltransferase (COMT) inhibitors, and others. The total levodopa equivalent daily dose (LEDD) of each PD participant at V0 and V1 were calculated based on a common standard 23 . Although Kiainik et al 24 reported no effect of medication on CVR in PD, to minimize the potential bias of medication in our study, we assessed MRI in the practically defined off state (>12 hours after antiparkinsonian medication intake).…”
Section: Methodsmentioning
confidence: 99%
“…The total levodopa equivalent daily dose (LEDD) of each PD participant at V0 and V1 were calculated based on a common standard. 23 Although Kiainik et al 24 reported no effect of medication on CVR in PD, to minimize the potential bias of medication in our study, we assessed MRI in the practically defined off state (>12 hours after antiparkinsonian medication intake). Depressive symptoms were assessed using the 30-item Chinese version of the Geriatric Depression Scale (GDS).…”
Section: Participantsmentioning
confidence: 95%